The role of electronic platforms in the educational process: Calligrapher platform as a model - Alashari, Duaa; Abdelaziz, Berghout; Sohsan, Imron (Thai-Nichi Institute of Technology (TNI), 2024)
Currently, electronic educational platforms play an extremely important role in providing free scientific content within the reach of community members. The Calligrapher platform is the first electronic platform for teaching Arabic calligraphy and Islamic decoration via the Internet, at the hands of an elite group of professional calligraphers, by providing several training courses. This study aims to shed light on the role of electronic platforms in the educational process, specifically the Al-Khattat electronic platform, and its effectiveness in the educational process. The importance of the study stems from it being the first study to address the definition of the effective and fruitful role achieved by the calligrapher platform in the educational process of Arabic calligraphy and Islamic decoration. The question in this context is the effective role it has achieved and the most prominent features of learning via digital platforms (the calligrapher platform is an example). The approach followed in this study is the case study approach, as it is consistent with the objectives and directions of the study. The study found that the electronic calligrapher platform is characterized by the multiplicity and diversity of training course tracks presented by senior specialized calligraphers and those with experience in Arabic calligraphy